Kalanchoe ser. Mpivady, a new series in K. subg. Calophygia (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae) - Smith, Gideon F. (Phytotaxa, 2025)
A new series, Kalanchoe ser. Mpivady (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae), is described in K. subg. Calophygia for three frutescent species and one nothospecies from Madagascar. Plants are shrubby with near-woody to woody stems at vegetative maturity; and have silvery white to golden brown spathulate to elliptic leaves; urceolate, often chromatic, succulent flowers; and small, but nonetheless conspicuous sepals. The new series fits in K. sect. Stellatopilosae of K. subg. Calophygia.